Measuring the density and bone mineral content of women in Mosul city - Jihan Fathi Yosef; khalid Majeed; Mushtaq Al-Jubbori (College of Education for Pure Sciences, 2023)
In this work, condition bone of women in an urban group has been measured and compared to a rural group. Based on the amount of bone mineral content (BMC) and bone mineral density (BMD), T-score and Z-score, in this study. From September 5, 2021 to February 28, 2022, a cross-sectional study was done at the DXA laboratory, Physiology Department, College of Medicine, University of Ninevah, Mosul, Iraq. Since 139 healthy females were enrolled through a college medical academic center's assessment. They were divided into two groups: rural (53 participants) and urban (86 participants). Studying the participants provided detailed anthropometric data. T-, Z-score, BMD and BMC were evaluated using a DXA bone densitometer scanner type (STRATOS) from the (DMS) group in France. All sample groups are classified according to age ranged between 30-79 years and divided into subgroups for every 10 years. The results showed that BMC and BMD values were higher in the rural group in comparison to the urban group for all age categories with a highly significant p = 0.0001.